2011
DOI: 10.1637/9636-122910-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Moving-Average Trigger for Early Detection of Rapidly Increasing Mortality in Caged Table-Egg Layers

Abstract: Rapidly increasing and unexplained mortality in commercial poultry flocks may signal the presence of a highly transmissible and reportable disease. Activation of an infectious-disease surveillance system occurs when a key production parameter, i.e., mortality, changes. Various triggers have been proposed to alert producers when mortality exceeds normal limits for a given production system to enable early detection of such diseases. In this article we demonstrate that a simple moving-average trigger is useful f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…After the declaration of an animal health emergency and establishment of a containment area, which initially may encompass large jurisdictional areas such as an entire U.S. state, the threshold for reporting by growers is expected to be much lower. Three‐times a seven‐day moving average has been shown to result in earlier reporting by producers and more closely represents a trigger for enhanced passive surveillance reporting of HPAI disease in caged table‐egg layers . This type of surveillance may become important in situations where laboratory capacity or other logistical factors delay the implementation of daily RRT‐PCR testing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After the declaration of an animal health emergency and establishment of a containment area, which initially may encompass large jurisdictional areas such as an entire U.S. state, the threshold for reporting by growers is expected to be much lower. Three‐times a seven‐day moving average has been shown to result in earlier reporting by producers and more closely represents a trigger for enhanced passive surveillance reporting of HPAI disease in caged table‐egg layers . This type of surveillance may become important in situations where laboratory capacity or other logistical factors delay the implementation of daily RRT‐PCR testing.…”
Section: Discussionmentioning
confidence: 99%
“…Multiples of a moving average were used as a trigger to simulate HPAI disease detection by a grower during a heightened awareness period following the establishment of the HPAI disease containment zone. In this option, a moving‐average trigger from the USDA, HPAI Secure Egg Supply Plan (SES Plan), in combination with an absolute‐mortality trigger was used .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This category considered mathematical models that were used to explore epidemiological and disease data related to surveillance and/or to evaluate distinct health measures (n = 20) [27,32,49,50,53,61,72,79,96,101,103,[109][110][111][112][113][114][115][116][117]. We found a wide range of models, such as linear, logistic, binomial, Poisson, time series, or CART.…”
Section: Regression Modellingmentioning
confidence: 99%
“…For an example of the former, a within-flock model was used to generate plausible outbreak data against which the efficacy of various outbreak detection methods were compared (Malladi et al, 2011). For an example of the latter, a within-flock model showed that vaccines conferring incomplete protection could counterintuitively increase the infectiousness of a flock, by delaying the time to detection and depopulation (Savill et al, 2006).…”
Section: Transmission Within Poultry Flocksmentioning
confidence: 99%